Mendelian nightmares: the germline-restricted chromosome of songbirds - Borodin, Pavel; Chen, Augustin; Forstmeier, Wolfgang; Fouché, Simone; Malinovskaya, Lyubov; Pei, Yifan; Reifová, Radka; Ruiz-Ruano, Francisco J; Schlebusch, Stephen A; Sotelo-Muñoz, Manuelita; Torgasheva, Anna; Vontzou, Niki; et al. (Chromosome research, 2022)
Germline-restricted chromosomes (GRCs) are accessory chromosomes that occur only in germ cells. They are eliminated from somatic cells through programmed DNA elimination during embryo development. GRCs have been observed in several unrelated animal taxa and show peculiar modes of non-Mendelian inheritance and within-individual elimination. Recent cytogenetic and phylogenomic evidence suggests that a GRC is present across the species-rich songbirds, but absent in non-passerine birds, implying that over half of all 10,500 bird species have extensive germline/soma genome differences. Here, we review recent insights gained from genomic, transcriptomic, and cytogenetic approaches with regard to the genetic content, phylogenetic distribution, and inheritance of the songbird GRC. While many questions remain unsolved in terms of GRC inheritance, elimination, and function, we discuss plausible scenarios and future directions for understanding this widespread form of programmed DNA elimination.
Keywords: Non-Mendelian inheritance; Phylogeny; DNA; B chromosome; Songbirds; zárodečné buňky; Germ Cells; Animals; Chromosome elimination; Germline-restricted chromosome; chromozomy; zpěvní ptáci; Chromosomes; sny; Germline/soma genome difference; zvířata; fylogeneze; Dreams